Water Nutrition and Quality Considerations for Cattle - Matt Hersom; Sonja Crawford (EDIS, 2008)
AN-195, a 4-page factsheet by Matt Hersom and Sonja Crawford, discusses water quality management issues for cattle, how to estimate water intake, quality factors such as pH, salinity, nitrates and nitrites, and contaminants and toxic elements. Includes references. Published by UF Department of Animal Sciences, February 2008.